A genetic study of the human T gene and its exclusion as a major candidate gene for sacral agenesis with anorectal atresia. Issue 3 (1st March 1999) - Papapetrou, Charalambos; Drummond, Felicity; Reardon, William; Winter, Robin; Spitz, Lewis; Edwards, Yvonne H
Abstract : Sacral agenesis is a heterogeneous group of congenital anomalies in which most cases are sporadic but rare familial forms also occur. Although one gene has been mapped to chromosome 7q36 in families with hemisacrum, associated with anorectal atresia and presacral mass, it is clear that the genetic aetiology of these disorders is complex and other genes remain to be discovered. Some years ago, the idea of T (Brachyury ) as a candidate gene for sacral agenesis was raised, because tail abnormalities associated with T and the t complex, on mouse chromosome 17, resemble spinal defects seen in man. The recent cloning and mapping of the human T gene prompted us to re-evaluate this idea. T is a transcription factor essential for the normal development of posterior mesodermal structures. Although the sequence and function of T are highly conserved in evolution, our genetic study shows that the coding region of the human gene is highly polymorphic. Three common variable amino acid sites in known functional domains have been identified: Gly356Ser, Asn369Ser, and Gly177Asp. For the latter variant, functional studies have shown that the presence of Asp at residue 177 reduces the stability of T dimer formation. A search for rare mutation of T in 28 selected patients with sacral agenesis/anorectal atresia identified a novel, rare variant in one patient and her mother. This mutation leads to an amino acid change within a conserved activation domain. While the functional significance of this single mutation requires further investigation, we can conclude from our studies that if T has a role in the aetiology of sacral agenesis, its contribution is small in this particular set of patients. However, we cannot exclude a more major role in other forms of sacral defect.